Growing from Our Roots: Strategies for Developing Culturally Grounded Health Promotion Interventions in American Indian, Alaska Native, and Native Hawaiian Communities - Walters, Karina L.; Johnson-Jennings, Michelle; Stroud, Sandra; Rasmus, Stacy; Charles, Billy; John, Simeon; Allen, James; Kaholokula, Joseph Keawe‘aimoku; Look, Mele A.; de Silva, Māpuana; Lowe, John; Baldwin, Julie A.; et al. (Prevention science, 2020)
Given the paucity of empirically based health promotion interventions designed by and for American Indian, Alaska Native, and Native Hawaiian (i.e., Native) communities, researchers and partnering communities have had to rely on the adaptation of evidence-based interventions (EBIs) designed for non-Native populations, a decidedly sub-optimal approach. Native communities have called for development of Indigenous health promotion programs in which their cultural worldviews and protocols are prioritized in the design, development, testing, and implementation. There is limited information regarding how Native communities and scholars have successfully collaborated to design and implement culturally based prevention efforts “from the ground up.” Drawing on five diverse community-based Native health intervention studies, we describe strategies for designing and implementing culturally grounded models of health promotion developed in partnership with Native communities. Additionally, we highlight indigenist worldviews and protocols that undergird Native health interventions with an emphasis on the incorporation of (1) original instructions, (2) relational restoration, (3) narrative-[em]bodied transformation, and (4) indigenist community-based participatory research (ICBPR) processes. Finally, we demonstrate how culturally grounded interventions can improve population health when they prioritize local Indigenous knowledge and health-positive messages for individual to multi-level community interventions.